2020
DOI: 10.21203/rs.3.rs-70872/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Substance Use, and Substance Use Disorder, in Relation to COVID-19: Protocol for a Scoping Review

Abstract: Background: The COVID-19 pandemic is creating severe issues for healthcare and broad social structures, exposing societal vulnerabilities. Among the populations affected by COVID-19 are people engaged in substance use, such as people who smoke, vape (e-cigarette use), use opioids, cannabis, alcohol, psychoactive prescription drugs, or have a substance use disorder (SUD).Monitoring substance use and SUD during the pandemic is essential, as people who engage in substance use or present with SUD are at greater ri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…That survey also showed that the logistic regression for generalized anxiety acted as a significant predictor for increased use of nicotine and other substances (12). This increase could be a reaction to the stress derived from the pandemic situation, as has previously been demonstrated in the outcomes of other studies researches carried out in Europe (34,35) and the United States (36). Smokers normally use certain drugs such as anxiolytics; there is a well-known close relationship between smoking and psychiatric disorders (a higher proportion of subjects with mental health disorders smoke, when compared to general population).…”
Section: Discussionsupporting
confidence: 54%
“…That survey also showed that the logistic regression for generalized anxiety acted as a significant predictor for increased use of nicotine and other substances (12). This increase could be a reaction to the stress derived from the pandemic situation, as has previously been demonstrated in the outcomes of other studies researches carried out in Europe (34,35) and the United States (36). Smokers normally use certain drugs such as anxiolytics; there is a well-known close relationship between smoking and psychiatric disorders (a higher proportion of subjects with mental health disorders smoke, when compared to general population).…”
Section: Discussionsupporting
confidence: 54%
“…Figure 1 summarizes immunogenetic factors discussed in the present review [ 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 ].…”
Section: Other Immune Response Genesmentioning
confidence: 99%
“…“Lifestyle” refers to habits (in terms of quality of nutrition, physical activity, drug consumption, smoking) and to socio-economic parameters (access to the health care system, level of education, access to high quality medical information), i.e., the social determinants of health. “Environment” (intended as exposure to contaminants, pollution, and non-ionizing radio frequency, but also as exposure to multiple pathogens) is relevant since it mechanistically modifies the immune response [ 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 ]. Viral genetic variants and their effects on virulence/COVID-19 severity are also a matter of intense research [ 211 , 212 , 213 ].…”
Section: Figurementioning
confidence: 99%
“…Being subjected to lockdown measures has been linked to an increased risk of hazardous drinking patterns and of alcohol use disorder (27). Furthermore, substance use appeared connected to an increased risk and severity of COVID-19 infections (28,29) and an increase in alcohol-related emergencies has been reported (29).…”
Section: Introductionmentioning
confidence: 99%